2014
DOI: 10.1039/c3cc45391j
|View full text |Cite
|
Sign up to set email alerts
|

Chemically doped perylene diimide lamellae based field effect transistor with low operating voltage and high charge carrier mobility

Abstract: Chemical doping of an electron transporter results in the formation of a radical anion containing semiconductor which showed high electron mobility (13 cm(2) V(-1) s(-1)) at low operating voltage (1 V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…14 As a proof, hydrazine-doped metalloorganic nanowires with ∼2 nm lamellae consisting of Zn 2+ doped N,N′-di(phenyl-3,5-dicarboxylic acid)-PDI radical anions have been used to construct efficient OFETs devices leading to a high electron mobility (13 cm 2 V −1 s −1 ) at a low operating voltage of 1 V under ambient conditions. 93 Further progress may be derived from the photoconductive 1D nanofibers of Lalanine-modified PDI in the presence of unusually air/waterstable perylene radical anions. 91 The fabrication strategy often imposes a significant effect on the morphology and sequent device performance.…”
Section: Ofetsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 As a proof, hydrazine-doped metalloorganic nanowires with ∼2 nm lamellae consisting of Zn 2+ doped N,N′-di(phenyl-3,5-dicarboxylic acid)-PDI radical anions have been used to construct efficient OFETs devices leading to a high electron mobility (13 cm 2 V −1 s −1 ) at a low operating voltage of 1 V under ambient conditions. 93 Further progress may be derived from the photoconductive 1D nanofibers of Lalanine-modified PDI in the presence of unusually air/waterstable perylene radical anions. 91 The fabrication strategy often imposes a significant effect on the morphology and sequent device performance.…”
Section: Ofetsmentioning
confidence: 99%
“…56 Many attempts have been made to unveil the relationships between the molecular structures of PDIs and OFET performances. 56,77,93 Commercially available molecules, PDI-C5, PDI-C8, and PDI-C13, have received considerable attention in this field. 56,77 Recent studies have demonstrated their bisolvent-phase selfassembled 1D nanowires feasible in fabricating n-type OFETs via the solution process (Figure 23a−c).…”
Section: Ofetsmentioning
confidence: 99%
“…11,12 Nevertheless a few stable n-type dopants have been reported via mechanisms other than integer charge transfer. [13][14][15][16][17][18][19][20][21][22][23][24][25] For example the addition of 1H-benzimidazole or benzimidazolium salts has succeeded in tuning of the work function of graphene and the conductivity of fullerene derivatives. 13,26 Mechanistic studies in the solution phase found that the dopant reacted with the fullerene derivative through hydride or hydrogen atom transfer to afford host radical anions, which were responsible for the doping effect.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we investigated the practical utility of bimetallic Pd‐ZnO nanohybrid materials for the preparation of dibromo perylenebiisimide (PBI) derivative (22) . The PBI derivatives are important due to their great applications in the field of material and supramolecular chemistry . As shown in Scheme , in the presence of bimetallic Pd‐ZnO nanohybrid materials the reaction between dibromoderivative (21) and phenylacetylene (13) afforded the desired product in 9 h in excellent (90 %) yield (Figure S68).…”
Section: Resultsmentioning
confidence: 99%